Law No. 18 Year 2003 Concerning Advocacy: Effectiveness Of Immunity Rights In Defending Clients - Nana Supiana; Evita Isretno Israhadi; Megawati Barthos (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
In carrying out their profession, advocates have the right to obtain information, data, and other documents needed to defend the interests of their clients, both from government agencies and other parties related to these interests. Advocates are free and without fear of issuing opinions or statements in court proceedings to defend the case for which they are responsible. Law on Advocates Number 18 of 2003 is to equalize the status of the Advocate profession with other legal professions Advocates as a vital element in the search for material truth in the judicial process, especially from the point of view of the client's legal interests. The regulation is intended to protect the public from legal services provided by advocates that are substandard. Law on Advocates Number 18 of 2003, also provides the right of immunity (immunity) to carry out their professional duties, and the interests of clients who are defended. The regulation regarding the immunity rights of advocates in Law no. 18 of 2003 Law on Advocates.